A 1D mathematical model for a microbial fuel cell - V. B. Oliveira (2013)
MFCs (microbial fuel cells) are a promising sustainable technology to meet increasing energy needs, especially using wastewaters as substrates, since they can generate electricity and accomplish wastewater treatment simultaneously. The MFC is a complex system involving bio-electrochemical processes, charge, mass and energy transfer. In this work, a steady state, one-dimensional model accounting for coupled heat, charge and mass transfer, and biofilm formation, along with the electrochemical reactions occurring in the MFC, similar to the ones developed for chemical fuel cells, is presented. The model predicts the correct trends for the influence of current density on the cell voltage, as well as, the influence of substrate concentration and temperature on the MFC performance and biofilm thickness. The model outputs are the temperature and concentration profiles and the biofilm thickness. The proposed model is rapidly and easily implemented and is therefore suitable for inclusion in real-time system level MFC calculations.